Por que uma educação para a democracia?: contribuições de Anísio Teixeira e Paulo Freire - Furtado, Lucas Alves (2025)
This study seeks to carry out a critical analysis of the works of Anísio Teixeira (1900– 1971) and Paulo Freire (1921–1997), with regard to the convergences and divergences of the concepts of education and democracy. The guiding research question is: why an education for democracy? In order to reflect on this question, the general objective was defined as investigating the contribution of the ideas of Anísio Teixeira and Paulo Freire toward an education for democracy. The specific objectives were also defined as follows: (1) to situate the historical-social and political context of the authors’ intellectual production; (2) to analyze the works of Anísio Teixeira and Paulo Freire concerning the concept of democracy and the education necessary for the formation of a democratic society; (3) to understand the scope of an education for democracy. The criteria for selecting the books were based on the authors’ philosophical and conceptual orientation regarding aspects of proximity in the concepts of education and democracy. The books selected by the first author were Educação e a crise brasileira (1956), Educação não é privilégio (1957), and Educação é um direito (1968), texts that were also read by Freire and cited in his 1959 work, and which express Anísio Teixeira’s mature educational philosophy. From Paulo Freire, the main works selected were Educação e atualidade brasileira (1959), Educação como prática de liberdade (1967), and Pedagogia do oprimido (1968). In addition, the study makes use of commentators of both authors, such as Clarice Nunes and Luís Viana Filho for Anísio Teixeira, and José Eustáquio Romão, Moacir Gadotti, and Fávero for Paulo Freire. During the selected period, from 1959 to 1967, Paulo Freire held ideas that converged with the philosophy of the Progressive Education or New School Movement, in addition to writing about democracy using the same or similar terms to those found in Anísio Teixeira’s works, and addressing the process of industrialization as a contributor to the process of democratization, or to the reconstruction of the democratic experience, ideas that are characteristic of Escola Nova thought and linked to the philosophy of John Dewey (1859–1952). The research is carried out based on Dilthey’s socio-historical epistemology within the historical-cultural model and a qualitative approach using Content Analysis methodology, seeking to understand the books of Anísio Teixeira and Paulo Freire beyond what is written, as situated within the experience of their own society. This is a bibliographical study, developed from the aforementioned books, grounded in theoretical contributions from the History and Philosophy of Education in their correlation with the construction of a democratic environment. The main results found were that education, in Anísio Teixeira and Paulo Freire, is a central condition for the formation of critical, autonomous, and historically conscious subjects, as well as an ethical and political process indispensable to the consolidation of participatory and dialogical practices in social life. It was also evidenced that education for democracy, in both authors, is configured as a historical project in permanent construction, linked to experience, dialogue, and the transformation of reality.